LEGAL PROTECTION FOR COMMUNITIES IN FOREST AREAS BASED ON LAW NO. 18 OF 2013 ON FOREST DESTRUCTION PREVENTION - Viarawangi, Fani Maria; Santoso, Imam; Kamal, Maulana (FOCUS: Jurnal of Law, 2025)
Deforestation in Indonesia poses a significant threat to the social and economic lives of forest adjacent communities. Despite the enactment of Law No. 18 of 2013 on the Prevention and Eradication of Forest Destruction, which includes provisions for legal protection of local communities, forest destruction rates remain high. This research aims to examine the form of legal protection for these communities, identify the challenges in implementing this protection, and propose strategies to enhance legal safeguards. The study adopts a normative-empirical legal approach, integrating statutory, conceptual, and sociological perspectives. Data was gathered through literature reviews and interviews with law enforcement officers, forestry officials, and local communities in Desa Nunuk, Kecamatan Maja, Kabupaten Majalengka. Findings reveal that, while legal protection exists, challenges such as limited resources, weak coordination, low legal awareness, and economic pressures hinder effective implementation. The study concludes that improving legal protection requires capacity building, legal education, better coordination, and sustainable livelihood alternatives for communities.